A method to analyze power output of vertical-axis wind turbines under rain - Nguyen Tuan Anh; Nguyen Huu Duc (Vietnam Journal of Science and Technology, 2018)
A method to analyze effect power output of a vertical axis wind turbine under rain is proposed. The rain had the effect of increasing the drag, slowing the rotational speed of the wind turbine and decreasing the power and performance. More and more ambitious projects for wind turbine production being set on many where on Vietnam, it is necessary to understand all the factors, especially by weather changes, that might affect wind power production. In this research, we lay out a model to estimate the effect of rainfall by simulating the actual physical processes of the rain drops forming on the surface of the blades of a vertical-axis wind turbine (VAWT), thereby determining optimal wetness, then power and performance respectively. This could have an effect on the control strategy necessary for designing and controlling wind turbine.